2005
DOI: 10.1016/j.febslet.2005.02.069
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological stress‐regulated gene expression in mice

Abstract: Eight genes showed significant changes in expression in mice under psychophysiological stress provided by cage-restraint and water-immersion. The transcription level of most of these genes was affected in all the tissues analyzed, and some of them were responsive genes in several different stress systems. Peculiarly, the expression level of one gene, cdc2-like kinase 1 (CLK1), was reduced only in the brain, while the balance of partially-and alternatively-spliced CLK1 mRNA species changed in all the tissues in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…This gene was at the top of the list of genes regulated, both, by dexamethasone in cultured astrocytes and by morphine in the mouse striatum. Alterations in the level of Sgk1 transcript or protein have been previously observed in the CNS in various models of stress (Koya et al, 2005;Murata et al, 2005;Yuen et al, 2010), after exposure to dexamethasone (Sato et al, 2008;David et al, 2005;van Gemert et al, 2006), drugs of abuse (Piechota et al, 2010b) and antidepressants (Conti et al, 2007), as well as in animal models of memory formation (von Hertzen and Giese, 2005) and neurodegeneration (Iwata et al, 2004;Rangone et al, 2004;Schoenebeck et al, 2005). Our results show that GR-responsive isoforms of Sgk1 are confined to astrocytes.…”
Section: Regulation Of Sgk1 Expression In Neural Cellssupporting
confidence: 73%
“…This gene was at the top of the list of genes regulated, both, by dexamethasone in cultured astrocytes and by morphine in the mouse striatum. Alterations in the level of Sgk1 transcript or protein have been previously observed in the CNS in various models of stress (Koya et al, 2005;Murata et al, 2005;Yuen et al, 2010), after exposure to dexamethasone (Sato et al, 2008;David et al, 2005;van Gemert et al, 2006), drugs of abuse (Piechota et al, 2010b) and antidepressants (Conti et al, 2007), as well as in animal models of memory formation (von Hertzen and Giese, 2005) and neurodegeneration (Iwata et al, 2004;Rangone et al, 2004;Schoenebeck et al, 2005). Our results show that GR-responsive isoforms of Sgk1 are confined to astrocytes.…”
Section: Regulation Of Sgk1 Expression In Neural Cellssupporting
confidence: 73%
“…We demonstrate that Sgk1 expression is regulated similarly in males and females, and is insensitive to the effects of handling. Previous work has demonstrated that even after a prolonged period of severe stress -6 hrs of restraint water submersion -a similar two-fold increase in Sgk1 mRNA levels could be detected (Murata et al, 2005), suggesting that a sufficiently strong stressor can cause rapid and persistent activation of Sgk1 in the hippocampus. Our finding that stress-induced Sgk1 induction is independent of corticosterone and Crhr1 is in contrast with in vitro studies that report increased Sgk1 expression by corticosterone in cultured hippocampal progenitor cells (Anacker et al, 2013), as well as by Crh via Crhr1 signaling (Sheng et al, 2008).…”
Section: Discussionmentioning
confidence: 87%
“…Thus, for the functional validation of some transcripts identified as possible drug targets, further studies will be necessary to assess the effect of transcriptional regulation in one or more rodent models of depression. [38][39][40][41][42][43] Another apparent limitation is that transcriptional profiles for the different treatments were compared only at the time points corresponding to clinical efficacy, which differed for each treatment being 2 days for ECT, 1 day for SD and 14 days for FLX. Thus, a comparative analysis of transcriptional changes induced at the same time points for all treatments is missing.…”
Section: Number Of Transcripts Affected By Single and Multiple Treatmmentioning
confidence: 99%
“…98 Sgk1 expression level is increased by acute amphetamine 36 and lysergic acid diethylamide (LSD) treatment, 36 and it is increased in the brain and peripheral tissues following psychosocial stress. 40 The upregulation of Sgk1 strongly correlates with the occurrence of cell death. In Mecp2-null mice, a model for Rett syndrome, 99 increased levels of Sgk1 mRNA are reported before and after onset of neurological symptoms.…”
Section: Number Of Transcripts Affected By Single and Multiple Treatmmentioning
confidence: 99%